Gram‐negative bacteremia in solid organ transplant recipients: Clinical characteristics and outcomes as compared to immunocompetent non‐transplant recipients. Issue 6 (21st November 2022) - Eichenberger, Emily M.; Troy, Jesse; Ruffin, Felicia; Dagher, Michael; Thaden, Joshua T.; Ford, Mandy L.; Fowler, Vance G.
Abstract: Background: Outcomes from Gram‐negative bacteremia (GNB) in solid organ transplant (SOT) recipients are poorly understood. Methods: This is a single center prospective cohort study comparing the clinical characteristics and outcomes of SOT recipients with GNB to immunocompetent non‐SOT patients with GNB between 1/1/2002 through 12/31/2018. Outcomes of interest included incidence of septic shock, respiratory failure, and time to death. A multivariable logistic regression model was used to determine factors associated with incidence of septic shock and respiratory failure. Time to death was evaluated using Cox proportional hazard models. Results: A total of 297 SOT and 1245 immunocompetent non‐SOT patients were included. Incidence of septic shock did not significantly differ between the groups (SOT 25.3% vs. non‐SOT 24.6%, p = .8225). Overall survival did not significantly differ by transplant status (30‐day survival: SOT 76%, 95% confidence interval [CI] 70, 92, non‐SOT 74%, 95% CI 71, 77: log rank: p = .76). SOT recipients taking three immunosuppressive medications had significantly lower odds of developing septic shock or respiratory failure requiring intubation and mechanical ventilation than those taking ≤1 agent (shock: adjusted odds ratio [aOR] 0.29, 95% CI 0.09, 0.90, p = .0316; respiratory failure: aOR 0.14, 95% CI: 0.04, 0.49, p = .0020). Conclusions: SOT recipients with GNB do not experience higher rates of septic shock, respiratory failure, or mortality than immnon‐SOT recipients with GNB. Among SOT recipients, a greater number of immunosuppressive medications may be associated with improved outcomes during GNB. Future studies are needed to understand the potential relationship between levels of immunosuppression and clinical outcome in SOT recipients with GNB. Abstract :